INDONESIA’S RESPONSES TOWARDS ROHINGYA REFUGEES: POLITICAL PERSPECTIVE - Komarudin, Ujang; Ayuningtyas, Dinda (Universitas Padjadjaran, 2024)
Rohingya refugees, originating from Myanmar, face significant challenges in Southeast Asia due to official non-recognition and systemic discrimination. Many seek refuge in neighboring countries like Indonesia. Employing qualitative research methods and an extensive literature review, this study investigates Indonesia’s responses to the Rohingya crisis from a political perspective. Additionally, building upon conflict resolution theory, it emphasizes the importance of dialogue, mediation, and compromise in addressing intricate crises. Furthermore, it explores concepts such as humanitarian diplomacy and regionalism, elucidating Indonesia’s role within ASEAN-led mechanisms. The research reveals key findings, showing Indonesia’s active participation in diplomatic initiatives addressing the Rohingya crisis, both bilaterally and within multilateral forums. Indonesia’s policy stances reflect a commitment to humanitarian principles and regional stability, emphasizing the protection of Rohingya rights. As a prominent member of ASEAN, Indonesia has leveraged regional platforms to advocate for collective action and effectively address the Rohingya crisis. This research sheds light on Indonesia’s role in addressing one of Southeast Asia’s most pressing humanitarian challenges, underscoring the importance of regional cooperation in finding sustainable solutions.